2010
DOI: 10.1111/j.1551-2916.2010.04097.x
|View full text |Cite
|
Sign up to set email alerts
|

Spin Spray‐Deposited Nickel Manganite Thermistor Films For Microbolometer Applications

Abstract: Nickel manganite thin films are good candidates for thermal imaging applications because of their large temperature coefficient of resistance (TCR), (>−3%/K) and good environmental stability. To enable low‐temperature deposition (90°C) on preexisting circuitry, a spin spray technique was developed for these materials. As‐deposited manganese oxide films show well‐developed X‐ray diffraction patterns, while as‐deposited nickel manganite films exhibit a nanocrystalline spinel structure. Low‐temperature (400°C) po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 42 publications
(83 reference statements)
2
20
0
Order By: Relevance
“…[12][13][14] Nevertheless, the pure NMO compound is still the subject of recent research efforts in order to establish new and more efficient synthesis routes [15][16][17][18][19][20][21] and thin and thick film production techniques. [22][23][24][25][26][27][28][29][30][31] Furthermore, the interplay between the physical properties and the Ni and Mn cation distribution on the tetrahedral and octahedral sublattices is still a matter of debate.…”
mentioning
confidence: 99%
“…[12][13][14] Nevertheless, the pure NMO compound is still the subject of recent research efforts in order to establish new and more efficient synthesis routes [15][16][17][18][19][20][21] and thin and thick film production techniques. [22][23][24][25][26][27][28][29][30][31] Furthermore, the interplay between the physical properties and the Ni and Mn cation distribution on the tetrahedral and octahedral sublattices is still a matter of debate.…”
mentioning
confidence: 99%
“…In previous study, we have also fabricated [(Ni 0.2 Mn 0.8 ) 1-x Cu x ] 3 O 4 (0.25 ≤ x ≤ 0.40) thin films using the metal-organic decomposition (MOD) method, and demonstrated that the thin films have high absolute TCR values (>3%/K) and low resistivity (<50 Ω cm) [4]. Although the TCR and resistivity outcomes are sufficient, it is not easy to apply them for use in an uncooled microbolometer because the annealing temperature is too high (450°C T annealing temperature (≤400°C) for the direct integration onto a substrate having complementary metal-oxide-semiconductor (CMOS) read-out circuitry [9].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is of interest to explore lower temperature methods compatible with CMOS integration. Spin spray deposition was used to prepare nanocrystalline nickel manganite films, at temperatures of 90°C . Reports of the formation of metastable, cation‐deficient, cubic nickel manganite spinel powders between 200°C and 400°C are also of interest.…”
Section: Introductionmentioning
confidence: 99%
“…In Refs. , reducing atmospheres, in some cases associated with the decomposition of organic precursors, were used to limit Mn oxidation. Higher oxidation states favor the formation of the bixbyite (Mn 2 O 3 ) and ilmenite (NiMnO 3 ) phases that are thermodynamically stable in air .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation